DINAMIKA KOMUNIKASI ORGANISASI MUHAMMADIYAH DIY DAN PENCALONAN SENATOR DPD RI DALAM TINJAUAN TEORI KEPRIBADIAN KELOMPOK RAYMOND CATTELL - Dani Fadillah (Universitas Muhammadiyah Jember, 2019)
This Paper aims to find out how the dynamics of Muhammadiyah's requirements in the Daerah Istimewa Yogyakarta during the 2019 election period on the candidate for the nomination of the senator who will serve as the board of Regional representative of the Republic of Indonesia. In conducting this research the author collects data in the form of polls and interviews with representatives of Muhammadiyah cadre of Daerah Istimewa Yogyakarta, then the data that authors acquire in the surgical use of personality theory that was triggered by Raymond Cattell as the surgical knife of the analysis. The results of this study show that Muhammadiyah still has to increase the political awareness of cadres to be more given the political situation. Even though the culture of an excellent organic cadre has established in the natural cadres of Muhammadiyah, Daerah Istimewa Yogyakarta, the culture needs to be maintained and enhanced to harmony in Muhammadiyah.